Islamic Educational Thoughts of Tuan Guru Haji (TGH) Muhammad Sholeh Chambali (Tuan Guru Bengkel) - Segaf Baharun (Al-Jadwa: Jurnal Studi Islam, 2022)
In every era, there are phenomenal events that impress people, full of astonishment and awe. In this context, admiration can be for objects, animals, or people so that it is referred to as "the center of attention/figure". What meant by a character by the author here is a person who has received general and broad recognition because of the depth of knowledge, piety, and noble character from the surrounding community or commonly called Ulama. In addition, there is still a lack of research participation by Indonesian Islamic education scholars on local Islamic education thinkers. Also, the possibility of conducting historical studies on local themes outside of economic and political aspects that have relevance to the life of the Indonesian nation, such as the thought of Islamic education, is expanding.